Sensitivity and specificity of Monte Carlo based independent secondary dose computation for detecting modulation-related dose errors in intensity modulated radiotherapy - Kowatsch, Matthias; Szeverinski, Philipp; Clemens, Patrick; Künzler, Thomas; Söhn, Matthias; Alber, Markus (Zeitschrift für medizinische Physik, 2025)
Background - The recent availability of Monte Carlo based independent secondary dose calculation (ISDC) for patient-specific quality assurance (QA) of modulated radiotherapy requires the definition of appropriate, more sensitive action levels, since contemporary recommendations were defined for less accurate ISDC dose algorithms. - Purpose - The objective is to establish an optimum action level and measure the efficacy of a Monte Carlo ISDC software for pre-treatment QA of intensity modulated radiotherapy treatments. - Methods - The treatment planning system and the ISDC were commissioned by their vendors from independent base data sets, replicating a typical real-world scenario. In order to apply Receiver-Operator-Characteristics (ROC), a set of treatment plans for various case classes was created that consisted of 190 clinical treatment plans and 190 manipulated treatment plans with dose errors in the range of 1.5-2.5%. All 380 treatment plans were evaluated with ISDC in the patient geometry. ROC analysis was performed for a number of Gamma (dose-difference/distance-to-agreement) criteria. QA methods were ranked according to Area under the ROC curve (AUC) and optimum action levels were derived via Youden’s J statistics. - Results - Overall, for original treatment plans, the mean Gamma pass rate (GPR) for Gamma(1%, 1mm) was close to 90%, although with some variation across case classes. The best QA criterion was Gamma(2%, 1mm) with GPR>90% and an AUC of 0.928. Gamma criteria with small distance-to-agreement had consistently higher AUC. GPR of original treatment plans depended on their modulation degree. An action level in terms of Gamma(1%, 1mm) GPR that decreases with modulation degree was the most efficient criterion with sensitivity=0.91 and specificity=0.95, compared with Gamma(3%, 3mm) GPR>99%, sensitivity=0.73 and specificity=0.91 as a commonly used action level. - Conclusions - ISDC with Monte Carlo proves highly efficient to catch errors in the treatment planning process. For a Monte Carlo based TPS, dose-difference criteria of 2% or less, and distance-to-agreement criteria of 1mm, achieve the largest AUC in ROC analysis.
Online verfügbar: 25. Oktober 2023, Artikelversion: 15. November 2025
Gesehen am 26.01.2026